A tight relationship between BOLD fMRI activation/deactivation and increase/decrease in single neuron responses in human association cortex - Marie-Alphée Laurent; Corentin Jacques; Xiaoqian Yan; Pauline Jurczynski; Sophie Colnat-Coulbois; Louis Maillard; Steven Le Cam; Radu Ranta; Benoit R Cottereau; Laurent Koessler; Jacques Jonas; Bruno Rossion (eLife)
The relationship between Blood-Oxygen-Level-Dependent (BOLD) responses in functional magnetic resonance imaging (fMRI) and increases or decreases in neural firing rate across human brain regions, especially the association cortex, remains largely unknown. Here, we contrast direct measures of neuronal activity in two adjacent brain regions of the fusiform gyrus (FG) associated with fMRI increases (lateral FG portion) or decreases (medial FG portion) of the same category-selective neural activity. In both individual brains tested across multiple recording sessions, a frequency-tagging stimulation objectively identified a substantial proportion (about 70%) of face-selective neurons. While single units recorded in the lateral FG showed a selective increase to faces, neurons localized in the medial FG decreased spiking activity selectively to faces. Beyond a relative reduction to faces compared to non-face objects, about a third of the single neurons found in the medial FG showed genuine suppression of baseline spiking activity upon presentation of a face. These observations clarify the nature of face-selective neural activity in the human brain, which can be expressed both as increases and active suppressions of spiking activity and, more generally, shed light on the physiological basis of the fMRI signal.